Factors Affecting Parents' Inclination Towards Private or Public Primary School - Mohd Kamal, Aiman Alif; Ab Malek, Haslinda; Azly, Nurernie Azwana; Musa, Qurratuaini (2020)
Education for children is one of the most concerning issues in the society especially among the parents. Recently, the numbers of private school in Malaysia are increasing rapidly. Despite the abundant of public school, demand for private school are still increasing. Therefore, this study aims to determine the most significant factors that affecting parents' decision in selecting private primary school for their children. Multistage sampling technique was used to determine the sample of 342 respondents. The factors included in this study were parent's income, parents' education level, teaching quality, school facilities and quality of education. Logistic regression analysis was used to determine the most significant factor since the dependent variable in this study was a binary categorical variable. It was found that parents with a diploma holder (p-value=0.004), parents with a degree holder (p- alue=0.002), parents' income (pvalue=0.001), and school facilities (p-value=0.000) were significant factors that influence parents' decision. In addition, results also found that the most significant factor that affecting parents' decision towards private primary school was parents with degree holder. It is hoped that this study will guide parents in selecting the best primary school for their children. Moreover, this study also benefits to the government in preparing strategy to develop defensive environment in public schools and to improve parents' satisfaction towards public primary school.